The Las Matras tonalitic-trondhjemitic pluton, Central Argentina: Grenvillian-age constraints, geochemical characteristics, and regional implications - Sato, Ana Maria (2000)
The N-S trending belt with Grenvillian-age rocks developed in central western Argentina represents the basement of an allochthonous terrane derived from Laurentia during the Early Paleozoic. The Las Matras pluton (36°46′S, 67°07′W) is located at the southern extension of this belt in the Las Matras Block. It consists of a low-Al tonalitic to trondhjemitic facies characteristic of an arc magmatism. Isotopic studies yielded Grenvillian Rb-Sr (1212 ± 47 Ma) and Sm-Nd (1188 = 47 Ma) ages which, due to the undeformed and non-metamorphosed character of the pluton, are interpreted to represent a crystallization age of around 1200 Ma. Although this age is slightly older than available dates from other exposures of the same belt, and the undeformed feature is also distinctive for Las Matras, the depleted Sr and Nd isotopic signatures of the pluton agree with those from other magmatic rocks involved in that belt. The differences found between Las Matras and the northern exposures indicate that this belt with Grenvillian-age rocks comprises regions of non-homogeneous evolution. Although the correlation of the Lower Paleozoic platform carbonates from the sedimentary cover of the Grenvillian-age basement rocks suggests the surroundings of the Southern Grenville Province (Texas and northern Mexico) as the probable detachment site for the Argentine belt, comparison of magmatic and tectonic processes involved in these basement rocks does not indicate similar evolutions. This fact can suggest an independent evolution of the Argentine belt prior to amalgamation to the Laurentian Grenville orogen. © 2000 Elsevier Science Ltd. All rights reserved.